«Существо дотоле невиданное» (рассказ «Уля» и оптическая тема в творчестве Андрея Платонова) [“Sushchestvo Dosele Nevidannoe”: Short Story “Ulya” And The Optical Theme In Andrei Platonov’s Works] - Yablokov, Yevgeni (Slavica Revalensia, 2019)
This article offers a comprehensive analysis of vision-related motifs in more than 30 works (both fictional and non-fictional) by Andrei Platonov. Its primary focus is aimed at a “children’s” short story Ulya (1939), which contains a whole series of vision-related motives representative of the writer’s artistic thinking. The analysis shows that the theme of vision combines “electromagnetic” and “ophtalmologic” discourses: the former refers, for instance, to the subject of the wholeness of the matter, while the latter consists of such motifs as “true” and “false” vision, etc. The article also explores some mythopoetic allusions in theshort story’s structure, and the relation of Ulya to literary tradition.